Urban land and housing markets in the Punjab, Pakistan - David E. Dowall; Peter Ellis (University of California, Institute of Urban and Regional Development (IURD), 2009)
Well-functioning urban land and housing markets are critical success factors for achieving robust economic growth. This paper provides an overview of urban land and housing market performance in Punjab Province of Pakistan. It describes the characteristics of well-functioning markets and argues that the Punjab's present markets are not performing. In fact, there exists a range of impediments to efficient urban land and housing market performance: excessive public land ownership, inadequate infrastructure services, weak property rights, counterproductive urban planning policies and regulations, costly subdivision and construction regulations, limited financing for property development and acquisition, rent controls, and distortive taxation mechanisms.
Keywords: 330